Multidimensional child deprivation trend analysis in Ethiopia: Further analysis of the 2000, 2005, and 2011 Demographic and Health Surveys - Plavgo, Ilze; Kibur, Martha; Bitew, Mahider; Gebreselassie, Tesfayi; Matsuda, Yumi; Pearson, Roger (DHS Further Analysis Reports No. 83, 2013)
This child-focused deprivation analysis sheds light on child poverty in Ethiopia, measuring child deprivation by using a number of dimensions of survival and development. It presents how different dimensions other than income poverty affect child well-being by using indicators from the Ethiopian Demographic and Health Surveys (2000, 2005 and 2011) and matching those to the rights contained in the CRC. The study measures the levels of child deprivation for the under-five child population and assesses overall progress in child deprivation reduction in Ethiopia over the years 2000 to 2011. The results show that while the deprivation incidence has decreased significantly in almost all dimensions between 2000 and 2011, the joint distribution of deprivations reveals that the percentage of children experiencing several deprivations at a time has decreased only marginally. In 2011, almost all children (94 per cent) still suffered from at least two deprivations considered as a threat to their survival or development. The average deprivation intensity was very high, children on average experiencing 3.8 deprivations at a time. This, however, is slightly lower compared to 2000 when children were on average deprived in 4.5 out of all six dimensions analysed. The deprivation overlap analysis shows differences in the extent to which the analysed sectors overlap, and reveals that children do not suffer from the same combinations of deprivations across regions. The study reveals significant disparities in multidimensional child deprivation levels between rural and urban areas and among regions
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents a trend analysis of multidimensional child deprivation based on data from the 2000, 2005, and 2011 Ethiopia Demographic and Health Surveys (EDHS). USAID and UNICEF coordinated the further analysis, and ICF International provided technical assistance. Irish Aid, USAID and MoFED provided the funding, the latter through the evaluation and research capacity building program supported by UNICEF. The opinions and arguments herein are those of the authors and do not necessarily reflect the views of the Government of Ethiopia, USAID, UNICEF, or Irish Aid. The Ethiopia Demographic and Health Surveys are part of a worldwide program that collects data on maternal and child health, nutrition, HIV/AIDS, fertility, family planning, and women’s empowerment. Additional information about the MEASURE DHS project can be obtained from: ICF International, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705, USA. Telephone:301-572-0200, Fax: 301-572-0999, E-mail:info@measuredhs.com, Internet: http://www.measuredhs.com